The impact of modern medical methods on reserve inheritance (The inheritance of pregnancy and mass death as an example) (Sebha University Conference Proceedings, 2024)
In the name of god, the most gracious, the most merciful, and may blessings and peace be upon the most honorable of the prophets and messengers and upon all his family and companions.As for what follows: The research deals with an important topic in the science of inheritance, which is reserve inheritance, which includes (the inheritance of pregnancy, the lost, the hermaphrodite, and collective death). These people inherit with discretion and precaution by making a reserved share until the condition of each of them becomes clear, whether the conditions for inheritance are met or not? This was due to modern medical methods. A prominent role in facilitating the estimation of their share of the estate, as jurisprudential studies have witnessed a remarkable development with regard to contemporary issues as a logical result of the developments witnessed in the reality of life, and the field of medicine and modern methods had the largest share in this development)